Кримінальна справа про пограбування церкви Чесного Хреста у Луцьку (1621 р.) - Яцишин, Михайло Михайлович; Yatsyshyn, Mykhailo M. (Громадська організація "Пенітенціарна асоціація України", 2018)
На підставі вивчення архівних матеріалів проаналізовано хід кримінальної справи про пограбування церкви Чесного Хреста у Луцьку в 1621 році.

The study of a particular criminal case is important for understanding all aspects of the judiciary functioning in the beginning of the seventeenth century in the region. The trial took place in the municipal courts of the Volyn Province on the basis of privileges, as well as German city law. Important factors influencing the course of the investigation, trial and sentence were confessional belongings of the person suspected and peson the guiety. A comprehensive historical and legal analysis of the criminal case about the robbery of the Church of the Holy Cross in Lutsk in 1621, the investigation and execution of the sentence of the suspect and the guilty in this article was made for the first time. The article analyzes the course of the criminal case about the robbery of the Holy Cross Church in Lutsk in 1621, examines the limits of authority in the field of criminal justice and the law court and the influence of the religious factor on the decision.
Criminal proceedings on the holy Cross Church in Lutsk (1621)
Keywords: Волинське воєводство; Луцький магістрат; міський суд; святокрадство; Volyn Province; Lutsk Magistrate; city court; sacrifice